Connectionist representations of tonal music : discovering musical patterns by interpreting artificial neural networks - Dawson, Michael Robert William, 1959- (desLibris. Books collection., 2018)
Intended to introduce readers to the use of artificial neural networks in the study of music, this volume contains numerous case studies and research findings that address problems related to identifying scales, keys, classifying musical chords, and learning jazz chord progressions. A detailed analysis of networks is provided for each case study which together demonstrate that focusing on the internal structure of trained networks could yield important contributions to the field of music cognition.